2014
DOI: 10.1002/anie.201403711
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium‐Catalyzed Reductive Methylation of Imines Using Carbon Dioxide and Molecular Hydrogen

Abstract: The use of the well-defined [Ru(triphos)(tmm)] catalyst, CO2 as C1 source, and H2 as reducing agent enabled the reductive methylation of isolated imines, as well as the direct coupling of amines with aldehydes and the subsequent reductive methylation of the in situ formed imines. The method, which afforded the corresponding N-methyl amines in very good to excellent yields, was also used for the preparation of the antifungal agent butenafine in one step with no apparent waste, thus increasing the atom efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(65 citation statements)
references
References 58 publications
0
56
0
9
Order By: Relevance
“…The yield of the target product (unsymmetrical tertiary amine) was 85 % if 1 a was used (Table , entry 8). Recently, Klankermayer and co‐workers showed that a Ru‐based molecular catalyst [Ru(triphos)(tmm)] in combination with HNTf 2 additives can selectively convert primary amines, aldehydes, and CO 2 to unsymmetrical tertiary amines . However, the use of aliphatic imines did not result in the formation of the reductively methylated product using this Ru‐based molecular catalyst.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The yield of the target product (unsymmetrical tertiary amine) was 85 % if 1 a was used (Table , entry 8). Recently, Klankermayer and co‐workers showed that a Ru‐based molecular catalyst [Ru(triphos)(tmm)] in combination with HNTf 2 additives can selectively convert primary amines, aldehydes, and CO 2 to unsymmetrical tertiary amines . However, the use of aliphatic imines did not result in the formation of the reductively methylated product using this Ru‐based molecular catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Recently,K lankermayer and co-workerss howedt hat aR ubased molecular catalyst[ Ru(triphos)(tmm)] in combination with HNTf 2 additives can selectively convert primary amines,a ldehydes, and CO 2 to unsymmetrical tertiary amines. [16] However, the use of aliphatic imines did not result in the formation of the reductively methylated product using this Ru-based molecular catalyst. In contrast, our Au/Al 2 O 3 -VS catalyst has the clear advantage of enablingt he constructiono fu nsymmetrical tertiary amines from all types of aliphatic amines and aldehydes.…”
Section: Reaction Pathway For the Methylation Of Aniline With Co 2 /Hmentioning
confidence: 87%
“…At the same time, they reported a possible utilization of CO 2 as N ‐methylation reagent. Subsequently, a more practical method for the direct N ‐methylation of aromatic amines with CO 2 and H 2 by a homogeneous Ru catalyst of Ru(triphos)(tmm) was reported by Klankermayer and co‐workers . Beller et al .…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a more practical method for the direct N-methylation of aromatic amines with CO 2 and H 2 by a homogeneous Ru catalyst of Ru (triphos)(tmm) was reported by Klankermayer and co-workers. [6] Beller et al [7] also found an improved catalyst with extended scope, in which aliphatic and aromatic amines as well as primary and secondary amines were tolerated by an in situ formed homogeneous Ru catalyst with LiCl or acid additives. However, homogeneous catalysts suffer from problems of catalyst/product separation, reusability, and the necessity of additives (acids, ligands, and salts) in the reaction system.…”
Section: Introductionmentioning
confidence: 99%
“…With the aim to devise new sustainable synthetic methods [10] that are able to make use of such nitrogen oxides, thus following the concept from "waste to value", [11] an ew accesst o oximes and aromatic amino acids could recently be developed using dilute nitrogen monoxide in air (Scheme 1, (1)). [12] Althought he obtained products are comparably valuable, this first strategyw as limitedt og as streams containingn itric monoxide in concentrations of at least 10 vol.…”
mentioning
confidence: 99%